Growing connections: exploring hands-on garden programs as a tool for food education and community outreach - Swaney, Madelynn (My University, 2025)
Many Americans are unaware of where their food comes from due to a significant disconnect between the broader population and their foodshed (Deelstra & Girardet 2017). This disconnect leads to uninformed adults and children not being able to identify the origins of food products (Newsela 2017). The rise of industrialized agriculture and the decline in the number of Americans involved in farming has contributed to a growing gap between people and the food production process. Most people rely on grocery stores for their food, and school curriculums often focus on what food is rather than how it is produced. Teaching students about food origins is essential, as it impacts eating decisions and habits which are formed in the early stages of development (Lineberger & Zajicek 2000; McAleese & Rankin 2007). Edible school garden programs offer hands-on opportunities to integrate food and nutrition education into schools, providing diverse and engaging learning experiences through gardening. This report examines the benefits of garden programs for students’s education, health, environmental stewardship, and academic performance. It reviews the literature on urban agriculture, edible school gardens, and various garden program models, including school gardens, university gardens, non-profit initiatives, and Indigenous food systems. To further understand these models, a selection of case studies will be analyzed. Through discussions with stakeholders, case study interviews, and site analysis, a projective design was developed to create a garden design and program for an Indigenous university. The findings inform both the design and development of a garden program, aiming to ensure that all members of the university can enjoy and benefit from the campus garden and greenhouse.
Keywords: Food education; Garden programs; Haskell Indian Nations University; Garden design; Garden program recommendations